2017
DOI: 10.1038/s41598-017-06924-3
|View full text |Cite
|
Sign up to set email alerts
|

Activation of TGF-β signaling induces cell death via the unfolded protein response in Fuchs endothelial corneal dystrophy

Abstract: Fuchs endothelial corneal dystrophy (FECD) is a slowly progressive bilateral disease of corneal endothelium in which accumulation of extracellular matrix (ECM) and loss of corneal endothelial cells (CECs) are phenotypic features. The corneal endothelium maintains corneal transparency by regulating water hydration; consequently, corneal endothelial dysfunction causes serious vision loss. The only therapy for corneal haziness due to corneal endothelial diseases, including FECD, is corneal transplantation using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 39 publications
3
44
1
1
Order By: Relevance
“…As in the differentiation of other professional secretory cells such as plasma cells [39], the increased flux of newly translated proteins represents a challenge to ER proteostasis and can lead to activation of ER stress response pathways, including ATF6 [40]. ATF6, along with other ER stress pathways, was reported to be activated with TGFβ treatment [41]. Furthermore, amelioration of ER stress, through treatment with chemical chaperones 4-PBA or TUDCA, has been shown to reduce fibrosis and TGFβ signaling [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…As in the differentiation of other professional secretory cells such as plasma cells [39], the increased flux of newly translated proteins represents a challenge to ER proteostasis and can lead to activation of ER stress response pathways, including ATF6 [40]. ATF6, along with other ER stress pathways, was reported to be activated with TGFβ treatment [41]. Furthermore, amelioration of ER stress, through treatment with chemical chaperones 4-PBA or TUDCA, has been shown to reduce fibrosis and TGFβ signaling [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatment options for preserving the release of functional ER calcium suppress cytokine-mediated beta cell death in diabetes 36 . Recently, ER stress was discovered to trigger the apoptosis of corneal endothelial cells through the intrinsic signaling pathway 37 , 38 . Thus, we postulated that the chronic elevation of aqueous cytokine levels may initiate the apoptosis of corneal endothelial cells via oxidative or ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group showed that ECM components, such as type I collagen and fibronectin, form aggregates of unfolded proteins in the corneal endothelium of FECD patients [ 41 ]. We also showed that activation of transforming growth factor-β (TGF-β) signaling causes a chronic overload of ECM proteins within the ER, which induces an accumulation of unfolded protein and activation of the intrinsic apoptotic pathway through the UPR [ 42 ]. The genetic background underlying the UPR induction is not yet elucidated; however, accumulating evidence supports a role for the UPR and associated apoptosis in FECD.…”
Section: Pathophisiologymentioning
confidence: 99%